Предмет: Алгебра,
автор: Аноним
решить уравнение (x+1)(x-1)(x-2)(x-4)=7
Ответы
Автор ответа:
0
решение уравнения
(x-1)(x-2)(x-3)(x-4)=840
(x^2-5x+4)(x^2-5x+6)=840
t=x^2-5x+4
t(t+2)=840
t^2+2t-840=0
t1=-30 t2=28
x^2-5x+4=-30 x^2-5x+4=28
x^2-5x+34=0 x^2-5x-24=0
действ. корней нет x1=-3 x2=8
(x-1)(x-2)(x-3)(x-4)=840
(x^2-5x+4)(x^2-5x+6)=840
t=x^2-5x+4
t(t+2)=840
t^2+2t-840=0
t1=-30 t2=28
x^2-5x+4=-30 x^2-5x+4=28
x^2-5x+34=0 x^2-5x-24=0
действ. корней нет x1=-3 x2=8
Похожие вопросы
Предмет: Алгебра,
автор: thankyouverymuch21
Предмет: Биология,
автор: kseniadovdenko7
Предмет: Қазақ тiлi,
автор: 20032003ae
Предмет: Право,
автор: xxxx123